PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN PERSEPSI TREND MAKEUP TERHADAP KEPUASAN PELANGGAN PADA JASA RIAS MAKEUP BYMEISA MOJOKERTO - Oktavia Citra Pratiwi; Irawati, Winaika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine and analyze the influence of service quality, price perception, and makeup trend perception partially and simultaneously on customer satisfaction at Makeup ByMeisa Mojokerto makeup services. This research used an associative quantitative method with data collection techniques through surveys using Likert-scale questionnaires distributed to 138 respondents. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. The results of the partial analysis showed that the service quality variable had a positive and significant effect on customer satisfaction with a t-count value of 6.236. The price perception variable also had a positive and significant effect on customer satisfaction with a t-count value of 7.614. In addition, the makeup trend perception variable had a positive and significant effect on customer satisfaction with a t-count value of 6.900. Simultaneous test results (F-test) showed that service quality, price perception, and makeup trend perception simultaneously had a significant effect on customer satisfaction with an F-count value of 27.879, which was greater than the F-table value. Based on the coefficient of determination (R²) test results, the variables of service quality, price perception, and makeup trend perception simultaneously contributed 39% to customer satisfaction. This indicates that customer satisfaction at Makeup ByMeisa Mojokerto is influenced by the quality of service provided, the suitability of prices with the benefits received by customers, and the ability of the makeup service to follow current makeup trends. Meanwhile, the remaining percentage is influenced by other variables not discussed in this study.